Globalization and smallholders: The adoption, diffusion and welfare impact of non-traditional export crops in Guatemala - Calogero Carletto; Angeli Kirk; Paul Winters; Benjamin Davis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper uses a duration analysis based on adoption data spanning over 25 years from six communities in the Central Highlands of Guatemala to explore how household characteristics and external trends play into both the adoption and diffusion processes of non-traditional exports among smallholders. Adoption was initially widespread and rapid, which led NTX to be hailed as a pro-poor success, reaching all but the smallest landholders. However, over time more than two-thirds of the adopters eventually dropped out from NTX production. Based on the analysis, NTX production appeared to have delivered less prosperity to adopters than initially promised. While smallholders may be enticed into entering into NTX markets when conditions are favourable, they may lack the capacity to overcome difficulties that inevitably arise in complex types of cultivations and in highly variable global agricultural markets. Governmental and non-governmental organizations can attempt to mitigate these difficulties, but market forces may overwhelm these efforts, with some adopters still unable to compete in global markets. – globalization ; land ; smallholders ; non-traditional exports
Keywords: J43; N56; O13; 330; Landwirtschaftlicher Kleinbetrieb; Agraraußenhandel; Globalisierung; Guatemala